A. Kulviečio bibliotekos autoriai ir knygos - Ročka, Marcelinas (Knygotyra, 1970)
We know about the library of A. Kulvietis only by a book list which has reached our days. But the list is incomplete and unreliable for in numerous instances no year or place of printing, no quantitative characteristics and sometimes even no name of the author or no title of the book are given. The aim of the present article is to supplement the list as far as possible so that a more exact picture of this first personal scientific library in Lithuania could be gained as because of this it is very important for the study of Lithuanian culture in the first half of the 16th century.